Information Sharing in Sweet Corn Supply Chain, Chiang Mai - Mahasorasak, Phattharakorn; Sinnarong, Nirote; Sintupuan, Somneuk; Ariyadet, Chalinda (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
Currently, the sweet corn marketing competition has led to an increasing awareness of supply chain management. Information sharing is one of the many ways which has been interested by researchers and supply chain members. Because it can increase supply chain efficiency and reduce costs. Nevertheless, motivating to information sharing is still a challenge. The purpose of this paper is to examine how trust, commitment, strategic alliance, opportunistic behavior and power influence on information sharing in sweet corn supply chain. In this study was analyzed using PLS-SEM. Drawing upon transaction cost theory and social exchange theory. Data were collected from 300 respondents comprise of growers, coordinators, integrators and producers,located in Chiang Mai. The results show that all paths have significant positive effects. Strategic alliance is crucial factor to information sharing that brings supply chain collaboration based on trust and commitment. Subsequently it improves a competitive advantage and has positive effect on long-term relationships.